Respectus Philologicus, 2011 Nr. 19 (24) - Bankauskaitė, Gabija (Respectus Philologicus, 2011)
CONTENTSI. PROBLEMS AND SOLUTIONSMichał Mazurkiewicz (Poland). Sport versus Religion... 11Natalia А. Kuzmina (Russia). Poetry Book as a Supertext... 19Jonė Grigaliūnienė (Lithuania). Possessive Constructions as a Purely Linguistic Phenomenon?... 31II. FACTS AND REFLECTIONSAleksandras Krasnovas, Aldona Martinonytė (Lithuania). Symbolizing of Images in Juozas Aputis Stories...40Jūratė Kumetaitienė (Lithuania). Tradition and Metamorphosis of Escapism (Running “from” or “into”) in the Modern and Postmodern Norwegian Literature...51Natalia V. Kovtun (Russia). Trickster in the Vicinity of Traditional Modern Prose...65Pavel S. Glushakov (Latvia). Semantic Processes in the Structure of Vasily Shukshin’s Poetics...81Tatyana Kamarovskaya (Belarus). Adam and the War...93Virginija Paplauskienė (Lithuania). Woman’s Language World in Liune Sutema’s Collection “Graffiti....99Jolanta Chwastyk-Kowalczyk (Poland). The Models of e-Comunication in the Polish Society of Britain and Northern Ireland...111Vilma Bijeikienė (Lithuania). How Equivocation Depends on the Way Questions are Asked: a Study in Lithuanian Political Discourse...123Viktorija Makarova (Lithuania). The One Who Names the Things, Masters Them: Ruskij vs. Rosijanin, Ruskij vs. Rosijskij in the Discourse of Russian Presidents...136Dorota Połowniak-Wawrzonek (Poland). Idioms from the Saga Film “Star Wars” in Contemporary Polish Language...144Ilona Mickienė, Inesa Birbilaitė (Lithuania). Women’s Naming in Telsiai Parish in the First Dacades of the 18th Century...158Liudmila Garbul (Lithuania). Reflection of Results of Interslavonic Language Contacts in the Russian Chancery Language of the First Half of the 17th Century (Synchronic and Diachronic Aspects). Part II...168Vilhelmina Vitkauskienė (Lithuania). Francophonie in Lithuania... 179Natalia V. Yudina (Russia). On the Role of the Russian Language in the Globalizing World of the XXI Century...189Maria Lojko (Belarus). Teaching Legal English to English Second Language Students in the US Law Schools...200III. OPINIONElena V. Savich (Belarus). On Generation of an Integrative Method of Discourse Analysis...212Marek Weber (Poland). Lexical Analysis of Selected Lexemes Belonging to the Semantic Field ‘Computer Hardware’...220IV. SCIENTISTS ABOUT SCIENTISTSOleg Poljakov (Lithuania). On the Female Factor in Linguistics and Around It... 228V. OUR TRANSLATIONSBernard Sypniewski (USA). Snake in the Grass. Part II. Translated by Jurga Cibulskienė...239VI. SCIENTIFIC LIFE CHRONICLEConferencesTatiana Larina (Russia), Laura Alba-Juez (Spain). Report and reflections of the 2010 International Conference on Intercultural Pragmatics and Communication in Madrid...246Books reviewsAleksandra M. Ponomariova (Russia). ЧЕРВИНСКИЙ, П. П., 2010. Номинативные аспекты и следствия политической коммуникации...252Gabija Bankauskaitė-Sereikienė (Lithuania). PAPLAUSKIENĖ, V., 2009. Liūnė Sutema: gyvenimo ir kūrybos keliais...255Yuri V. Shatin (Russia). Meaningful Curves. ГРИНБАУМ, О. Н., 2010. Роман А.С. Пушкина «Евгений Онегин»: ритмико-смысловой комментарий... 259Journal of scientific lifeDaiva Aliūkaitė (Lithuania). The Idea of the Database of Printed Advertisements: the Project “Sociolinguistics of Advertisements”...263Loreta Vaicekauskienė (Lithuania). The Project “Vilnius is Speaking: The Role of Vilnius Language in the Contemporary Lithuania, 2010”...265Daiva Aliūkaitė (Lithuania). The Project “Lithuanian Language: Fractures of Ideals, Ideologies and Identities”: Language Ideals from the Point of View of Ordinary Speech Community Members...267Announce...269VII. REQUIREMENTS FOR PUBLICATION...270VIII. OUR AUTHORS...278
Keywords: none